Exploring Fatal and Non-Fatal Violence Against Parents: Challenging the Orthodoxy of Abused Adolescent Perpetrators - Holt, Amanda (International journal of offender therapy and comparative criminology, 2018)
An examination of scholarly literature concerning fatal violence (i.e., parricide) and non-fatal violence toward parents reveals dominant themes of mental illness, child abuse, and pathology based on a research paradigm that focuses on adolescent perpetrators and, to a lesser extent, elderly victims. This article presents a critical analysis of this literature and argues for a more contextualized approach to the study of violence against parents. It is argued that criminologists should widen their methodological lens to examine this issue from a life course perspective and draw on conceptual tools such as developmental pathways, sources of conflict, and intersectionality to allow for an analysis that can offer new ways of thinking about violence toward parents.